THE KONSEPSI KEPEMILIKAN SOSIAL DALAM PERLINDUNGAN INDIKASI GEOGRAFIS PALA KABUPATEN ACEH SELATAN - Effida, Dara Quthni; Aulia, Eza; Maulana, Jefrie (Faculty of Law, Universitas Pasundan, 2023)
Indonesian GIs is still little than of their leading commodities that have the potential to receive legal protection as GIs. One of them is South Aceh's nutmeg as leading commodities. The research question revolves around the concept of social ownership within the legal protection framework of South Aceh Nutmeg's geographical indication and how its legal protection operates. This study aims to elucidate the concept of social ownership concerning the legal protection potential of South Aceh Nutmeg's geographical indication. This research employs a normative juridical method using legislative analysis and a conceptual approach. The registration of geographical indications is vital for securing legal protection concerning social ownership rights and the product's regional origin. Geographical indications serve as instruments to protect products possessing unique geographical characteristics, acting as a claim to social ownership for the communities producing these goods. There are four fundamental principles in developing the concept of social ownership: active participation, sustainable management, responsibility in preservation, and equitable benefit-sharing. The development of social ownership concepts is anticipated to resolve issues related to the deserving and fair legal protection of the South Aceh Nutmeg Geographical Indication. Keyword: Social Ownership, Geographical Indication, Nutmeg, South Aceh.